Ligand Engineering toward the Trade‐Off between Stability and Activity in Cluster Catalysis - Guan, Zong‐Jie; He, Rui‐Lin; Yuan, Shang‐Fu; Li, Jiao‐Jiao; Hu, Feng; Liu, Chun‐Yu; Wang, Quan‐Ming (Angewandte Chemie International Edition, 2022)
We report the structures, stability and catalysis properties of two Ag21 nanoclusters, namely [Ag21(H2BTCA)3(O2PPh2)6]SbF6 (1) and [Ag21(C≡CC6H3‐3,5‐R2)6(O2PPh2)10]SbF6 (2) (H4BTCA=p‐tert‐butylthiacalix[4]arene, R=OMe). Both Ag21 structures possess an identical icosahedral kernel that is surrounded by eight peripheral Ag atoms. Single‐crystal structural analysis and ESI‐MS revealed that 1 is an 8‐electron cluster and 2 has four free electrons. Theoretical results show that the P‐symmetry orbitals are found as HOMO‐1 and HOMO states in 1, and the frontier unoccupied molecular orbitals (LUMO, LUMO+1 and LUMO+2) show D‐character, indicating 1 is a superatomic cluster with an electronically closed shell 1S21P6, while 2 has an incomplete shell configuration 1S21P2. These two Ag21 clusters show superior stability under ambient conditions, and 1 is robust even at 90 °C in toluene and under oxidative conditions (30 % H2O2). Significantly, 2 exhibits much higher activity than 1 as catalyst in the reduction of 4‐nitrophenol. This work demonstrates that ligands can influence the electronic structures of silver clusters, and further affect their stability and catalytic performance. Two diphenylphosphonate‐protected silver nanoclusters, [Ag21(H2BTCA)3(O2PPh2)6]SbF6 (1) and [Ag21(C≡CC6H3‐3,5‐R2)6(O2PPh2)10]SbF6 (2), have identical icosahedral kernels but different number of free electrons. Cluster 2 exhibits much higher activity than the more stable 1 in the catalytic reduction of 4‐nitrophenol. This work shows that the electronic structures of metal nanoclusters can be modulated via different combinations of ligands.